2011
DOI: 10.1097/aap.0b013e318228cdb0
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Release and Neurologic Impairment After Intrathecal Administration of Lidocaine and Bupivacaine in the Rat

Abstract: Intrathecal lidocaine caused a concentration-dependent increase of the CSF glutamate release and postinjection neurologic impairment; these effects can be reversed by MK-801. However, intrathecal bupivacaine shows no influence. We suggest that glutamate may be involved in the pathogenesis of lidocaine-induced spinal neurotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Nevertheless, studies using higher concentrations of lidocaine than those used in the present study have shown that the drug is highly toxic for the nervous tissue [38], and for neuronal cultures [39,40]. In addition, it is well known that 2.5% to 10% lidocaine concentrations induce severe cytotoxic effects even when administered by the intravenous, epidural or intrathecal route [41][42][43]. In vivo studies conducted by Hampl et al [44] showed that 2% lidocaine administered by intrathecal route did not cause histopathologic or structural changes in the spinal cord, while studies performed by Ready et al [45] reported that spinal cord histopathologic changes and neurologic deficits occurred with lidocaine concentrations beyond 8%.…”
Section: Discussionmentioning
confidence: 60%
“…Nevertheless, studies using higher concentrations of lidocaine than those used in the present study have shown that the drug is highly toxic for the nervous tissue [38], and for neuronal cultures [39,40]. In addition, it is well known that 2.5% to 10% lidocaine concentrations induce severe cytotoxic effects even when administered by the intravenous, epidural or intrathecal route [41][42][43]. In vivo studies conducted by Hampl et al [44] showed that 2% lidocaine administered by intrathecal route did not cause histopathologic or structural changes in the spinal cord, while studies performed by Ready et al [45] reported that spinal cord histopathologic changes and neurologic deficits occurred with lidocaine concentrations beyond 8%.…”
Section: Discussionmentioning
confidence: 60%
“…It is well established that local anesthetics can cause neurotoxicity (Sakura et al, ). Several mechanisms regarding its neurotoxicity have been proposed including the increase of glutamate release (Cherng et al, ) and the activation of MAPK (Haller et al, ; Lirk et al, ). However, the concentrations of local anesthetics used in the studies cited above are equal to or even higher than the concentrations for local anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Goyagi et al () found that local anesthetics protect against ischemia‐induced brain injury without the alteration of glutamate concentration. Moreover, Cherng et al () reported that local anesthetics may evoke neurotoxicity through the increase of glutamate concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral Tests The Basso, Beattie, and Bresnahan (BBB) scale, ranging from 0 (no movement) to 21 (normal movement), was used to assess the locomotor function of the hind limbs as previously described. 14) BBB scoring was performed on a mat four times for each rat on days 1-4. Each test was conducted for 5 min by two researchers with no knowledge of the experimental groups.…”
Section: Animals and Experimental Protocolmentioning
confidence: 99%